Upaya Kesetaraan Gender dalam Pemikiran K.H. Husein Muhammad - Mochamad Ziaul Haq; Audrey Diva Azzahra Arief; Lathifah Mumtazah; R.F. Bhanu Viktorhadi (Equalita: Jurnal Studi Gender dan Anak, 2023)
Feminism is one of the most campaigned issues that happened because in reality, gender equality is not done properly. The womankind are often discriminated against and become the victim from this act violence so an urgency to uphold women’s rights. To spread the gender equality spirit, lots of efforts have been done. K.H. Husein Muhammad is one of the figures that has been fighting for gender equality in Indonesia by establishing the Fahmina Institute and writing articles and books containing certain messages to spread gender equality, specifically women’s rights. This writing will begin with an introduction followed by a biography and the results of K.H. Husein Muhammad’s thought to answer the question relating his contribution and the impact of said contribution to gender equality in Indonesia. The information contained in this writing is sourced from trusted sources such as journal articles, trusted sites and news.